DEVELOPMENT OF MEDIA CARD GAME VEROES (VERTEBRATES NEURO SYSTEM) FOR TRAINING REASONING SKILLS OF SMA STUDENTS ON NERVOUS SYSTEM MATERIALS - Jefri Nugroho; Murni Ramli (EDUSAINS, 2022)
This research was conducted because of the difficulties of students in learning the material on the nervous system. This research aims to produce Veroes Card Game learning media to train students' reasoning skills. This research is a mix method research carried out in two stages, namely the media preparation stage and the media feasibility test stage. The subjects used in the feasibility test of the media were public and islamic high school teachers in Sukoharjo regency and students majoring in biology and science education. The data collection technique is done by the feasibility test of the media using a questionnaire instrument. Data analysis of the feasibility test results were analyzed by Analysis of the Rasch Model using Winstep application. From the results of data analysis the instrument item reliability value obtained was 0.92, the respondent's reliability value was 0.89 and the Cronbach Alpha value was 0.93 so that it could be stated in very good category. The probability value of instrument items has a range of values above 5% (0.05) with three instrument items detected contain bias. Based on the research results, it can be stated that the Card Game Veroes media has met the criteria as a suitable learning medium to use in the learning process on the nervous system material.PENGEMBANGAN MEDIA CARD GAME VEROES (VERTEBRATES NEURO SYSTEM) UNTUK MELATIH REASONING SKILLS SISWA SMA PADA MATERI SISTEM SARAFAbstrakPenelitian ini dilaksanakan karena adanya kesulitan siswa dalam mempelajari materi sistem saraf. Penelitian bertujuan untuk menghasilkan media pembelajaran Card Game Veroes untuk melatih reasoning skills siswa. Penelitian ini merupakan penelitian mix method yang dilaksanakan dengan dua tahap, yaitu tahap penyusunan media dan tahap uji kelayakan media. Subjek yang digunakan dalam uji kelayakan media adalah Guru SMA/MA wilayah Kabupaten Sukoharjo dan mahasiswa jurusan pendidikan biologi dan IPA. Teknik pengumpulan data dilakukan dengan uji kelayakan terhadap media menggunakan instrumen angket. Analisis data hasil uji kelayakan dianalisis menggunakan Analisis Model Rasch dengan aplikasi Winstep. Dari hasil analisis data diperoleh nilai reliabilitas item instrumen sebesar 0,92, nilai realibilitas responden sebesar 0,89 dan nilai Alpha cronbach sebesar 0,93 sehingga dapat dinyatakan dalam kategori sangat bagus. Nilai probabilitas item instrumen memiliki kisaran nilai diatas 5% (0,05) dengan tiga item instrumen yang terdeteksi mengandung bias.Berdasarkan hasil penelitian, dapat dinyatakan media Card Game Veroes telah memenuhi kriteria sebagai media pembelajaran yang layak untuk digunakan dalam proses pembelajaran pada materi sistem saraf.How To Cite: Nugroho,, J., Ramli, M. (2022). Pengembangan Media Card Game VEROES (Vertebrates Neuro System) Untuk Melatih Reasoning Skills Siswa SMA Pada Materi Sistem Saraf. EDUSAINS, 14 (1) : 63-71